Quantitative aspects of mining induced seismicity in a part of the Welkom Goldfield /cRicardo Isidro Loureiro Ferreira. - Ferreira, Ricardo Isidro Loureiro. (My University, 1997)
Rockbursts continue to be one of the more high profile and problematic worker hazards in the South African gold mining industry. Recent advances in the technology of seismic monitoring systems and seismic data analysis and interpretation methods hold considerable promise towards improving the success rate of rockburst control measures. This study tests different methods for the evaluation of the response of geological structures to mining induced stress changes. A small part of Western Holdings Gold Mine in the Welkom goldfield -- the Postma Area -- offers a challenge because of its geological complexity, accessibility and high incidence of seismicity. The sensitivity of the local network to ground motions in this area of interest and the expected spatial location accuracy is established and deemed adequate for a detailed investigation of seismic activity. The local mining geometry, geology and methods of mining are discussed. The fractured state of the rock mass observed in situ, close to the stope faces, is in agreement with the results of numerical elastic modelling and the high stresses inferred seismically. Almost immediately after the incidence of a large event (ML 3.7) which occurred close to one end of a dyke, an increased rate of seismic activity became apparent at another part of the same dyke, some 250 m to the east. A change in the state of seismic stress, before and after the large event, points to a transfer of stress along this geological discontinuity. A quantitative analysis of recorded seismicity indicates spatial and temporal variations in the state of stress and strain throughout the rock mass surrounding Mining excavations. The elastic stress modelling performed routinely by rock mechanics engineers in the deep gold mines is, by itself, incapable of catering for the rheological nature of the rock mass, but taken together with independent seismic evaluations of a fault orthogonal to a highly stressed dyke it is shown that both methods are mutually complementary and can enhance the assessment of the seismic instability of the structures. A back-analysis is conducted on ten large seismic events (ML 2.5) to identify precursors. These show that the timely recognition of high gradients in physical seismic parameters pertaining to strain rate and stress in time and space immediately prior to major seismic events is a real and practical possibility, as such constituting an early warning mechanism. The fore-warning of a large event is best served by an analysis of seismicity over the short term (weeks or days) through time-history variations and/or contouring of various seismic parameters, although long-term seismic responses (months or weeks) characterise specific patterns and trends which are useful in the forecast.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Geophysics .
Keywords: Induced seismicity -- South Africa.; Seismic prospecting -- South Africa.; Welkom Goldfield.; Gold mines and mining -- South Africa.